2014
DOI: 10.1128/jvi.01425-14
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus 71 3C Inhibits Cytokine Expression through Cleavage of the TAK1/TAB1/TAB2/TAB3 Complex

Abstract: Enterovirus 71 (EV71) causes hand, foot, and mouth disease in young children and infants. Severe infection with EV71 can lead to various neurological complications or fatal diseases. However, the mechanism of EV71 pathogenesis is poorly understood. Emerging evidence suggests that EV71 modulates type I interferon (IFN) and cytokine responses. Here, we show that EV71 disables components of the TAB2 complex through the 3C protein. When expressed in mammalian cells, EV71 3C interacts with TAB2 and TAK1, which inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
87
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 40 publications
0
87
0
Order By: Relevance
“…Several host factors have been found to be cleaved by 3C (9)(10)(11)(12). In this study, we identified PinX1 as a novel target of EV71 3C.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Several host factors have been found to be cleaved by 3C (9)(10)(11)(12). In this study, we identified PinX1 as a novel target of EV71 3C.…”
Section: Discussionmentioning
confidence: 77%
“…It has been reported that 3C cleaves cellular CstF-64 protein, which inhibits host RNA processing and polyadenylation (9). Interferon-regulatory factor 7 (IRF7) (10), TIR domain-containing adaptor inducing beta interferon (TRIF) (11) and the TAK1/TAB1/ TAB2/TAB3 complex (12) are also substrates of 3C, and the cleavage of these factors plays important roles in antiviral immune evasion.…”
mentioning
confidence: 99%
“…Several studies have suggested that EV71 suppresses antiviral immunity (9,10,(13)(14)(15)(16)(17). In addition to inhibition of type I IFN induction, EV71 has evolved strategies to counter inflammasome activation through cleavage of NLRP3 by viral proteases 2A and 3C (18).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the 3C protease induces apoptosis by inducing cleavage of PinX1, an intrinsic telomerase inhibitor, to facilitate EV71 release (12). Other important roles of 3C are to dampen immune responses by impeding the RIG-I-MAVS interaction or by cleaving a series of host factors, including TIR domain-containing adaptor inducing IFN-␤ (TRIF), interferon regulatory factor 7/9, and TAK1/TAB1/TAB2/TAB3 complex (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…It possesses both proteolytic and RNA binding activities (32,33), which enable the protease to perform multiple tasks in systems involving viral replication and pathogen-host interactions. Increasing evidence suggests that EV-A71 3C pro targets innate immune factors, such as RIG-I, TRIF, IRF7/9, the TAK1/TAB1/TAB2/TAB3 complex, and NLRP3, to modulate type I IFN and cytokine responses (34)(35)(36)(37)(38). Recently, EV-D68 3C pro has been reported to target IRF7 and TRIF to disable innate sensing responses (39,40).…”
mentioning
confidence: 99%